Condições sociais, espaços sociais e a construção das expectativas de futuro: prolongamentos e avanços a partir da tese da causalidade do provável de Pierre Bourdieu - Santos, Harlon (2026)
When analyzing the construction of future expectations and/or aspirations, Bourdieu presents the concept of the causality of the probable, proposing that the set of future projections is engendered by social conditions of origin, resulting in a probable future as a consequence of the adjustment between these expectations and the conditions for their realization. This theoretical proposition was crucial for the field of sociology of education, specifically for studies on educational expectations, reverberating in analyses of educational trajectories, school longevity, and social mobility. This centrality of the Bourdieusian paradigm of socialization generated, with similar force, theoretical tensions and divergences that contest the interpretive meaning regarding the formation and/or generation of these expectations and their capacity as future orienteers in student trajectories. This article (i) presents a brief bibliometric survey on the use of this concept in the production of Sociology of Education in Brazil and Latin America and (ii) offers a theoretical discussion about the limits and potential reinterpretations of the concept of the causality of the probable, based on empirical results and theoretical debates on the theme of future expectations in the field of Sociology of Education subsequent to Bourdieu. Revisiting this Bourdieusian thesis considering recent discussions on the topic of student expectations allows for an evaluation of the capacity of the incorporated past to determine the trajectories of individuals, while also considering the present of the action, its contexts, and social spaces that may or may not prefigure new expectations and peculiar trajectories.